Biocompatibility of gold nanoparticles in retinal pigment epithelial cell line. (December 2016) - Karakoçak, Bedia Begüm; Raliya, Ramesh; Davis, Josh T.; Chavalmane, Sanmathi; Wang, Wei-Ning; Ravi, Nathan; Biswas, Pratim
Abstract: Gold nanoparticles (Au NPs) have been tested as targeted delivery agents because of their high chemical stability and surface plasmon properties. Here, we investigated the biocompatibility of Au spheres (5-, 10-, 20-, 30-, 50-. and 100-nm), cubes (50-nm), and rods (10 × 90 nm) on a retinal pigment epithelial (ARPE-19) cell line. The lethal dose for killing 50% of the cells (LD50 ) was evaluated using an MTT (3-[4, 5 dimethyl-thiazoly-2-yl] 2-5 diphenyl tetrazolium bromide) assay. At and above LD50, based on mass concentrations, the confluent cell layer began to detach, as shown by real-time measurements of electric impedance. We found that the biocompatibility of spheres improved with increasing nanoparticle size. The Au rods were less biocompatible than 10-nm spheres. Confocal microscopy showed that cubic (50-nm) and spherical NPs (50- and 100-nm) neither had cytotoxic effects nor entered cells. Lethal doses for internalized spherical NPs, which were toxic, were recalculated based on surface area (LD50, A ) concentrations. Indeed, when biocompatibility was expressed as the surface area concentration of NPs, the curve was independent of size. The LD50, A of Au nanospheres was 23 cm 2 /ml. Our findings demonstrate that the sole modulation of the surface area would make it possible to use Au NPs for therapeutic purposes. Graphical abstract: Highlights: Two independent methods were used for the biocompatibility testing: electric cell-substrate impedance sensing and MTT assay. The confocal images showed that 5-30 nm spheres and 10×90 nm rods were internalized unlike 50-100 nm spheres and 50 nm cubes. Similar sized nanospheres and nanorods were both internalized; however, nanorods were less biocompatible than nanospheres. With comparable surface area concentrations (23 cm2/ml), spherical Au NPs in the range of 5–30 nm have similar biocompatibility.